Chronic hypoxia promoted pulmonary arterial smooth muscle cells proliferation through upregulated calcium‐sensing receptorcanonical transient receptor potential 1/6 pathway. (15th June 2021) - Xu, Juan; Wen, Xing; Fu, Zhenli; Jiang, Yongliang; Hong, Wei; Liu, Rongmin; Li, Shaoxing; Cao, Weitao; Pu, Jinding; Huang, Lingmei; Li, Bing; Ran, Pixin; et al.
Abstract: Objectives: Although both calcium‐sensing receptor (CaSR) and canonical transient receptor potential (TRPC) proteins contribute to chronic hypoxia (CH)‐induced pulmonary arterial smooth muscle cells (PASMCs) proliferation, the relationship between CaSR and TRPC in hypoxic PASMCs proliferation remains poorly understood. The goal of this study was to identify that CH promotes PASMCs proliferation through CaSR‐TRPC pathway. Methods: Rat PASMCs were isolated and treated with CH. Cell proliferation was assessed by cell counting, CCK‐8 assay, and EdU incorporation. CaSR and TRPC expressions were determined by qPCR and Western blotting. Store‐operated Ca 2+ entry (SOCE) was assessed by extracellular Ca 2+ restoration. Results: In PASMCs, CH enhanced the cell number, cell viability and DNA synthesis, which is accompanied by upregulated expression of CaSR, TRPC1 and TRPC6. Negative CaSR modulators (NPS2143, NPS2390) inhibited, whereas positive modulators (spermine, R568) enhanced, the CH‐induced increases in cell number, cell viability and DNA synthesis in PASMCs. Knockdown of CaSR by siRNA inhibited the CH‐induced upregulation of TRPC1 and TRPC6 and enhancement of SOCE and attenuated the CH‐induced enhancements of cell number, cell viability and DNA synthesis in PASMCs. However, neither siTRPC1 nor siTRPC6 had an effect on the CH‐induced CaSR upregulation, although both significantly attenuated the CH‐induced enhancements of cell number, cell viability and DNA synthesis in PASMCs. Conclusion: These results demonstrate that upregulated CaSR‐TRPC1/6 pathway mediating PASMCs proliferation is an important pathogenic mechanism under hypoxic conditions.